Water Use in Carp Polyculture: Effects on Rearing Environment and Water Productivity - MOHANTY, R K; MISHRA, A; MANDAL, K G; PANIGRAHI, P; AMBAST, S K (Journal of the Indian Society of Coastal Agricultural Research, 2017)
This study was carried out in farmers’ fields to quantify the total and consumptive water use (CWU) in carp polyculture under different water management protocols. Treatment-wise estimated total crop water requirement ha-1 (culture duration-180d) was 3.69, 4.62 and 3.9 ha-m, while the computed consumptive water use index (m3 kg-1 biomass) was 6.62, 9.31 and 7.08, in T1 (no water exchange), T2 (10% water exchange on monthly basis) and T3 (10% water exchange depending on the water quality variables), respectively. Water use in ponds usually varies with the intensity of production, frequency and amount of water exchange employed. Higher the amount of water exchange, higher is the total water use (TWU) as in case of T2. Various hydro-biological parameters prevailing in the different treatments were within the optimum 2 ranges and did not fluctuate drastically. This was probably due to the similar levels of inputs in all the treatments in the form of organic manure, inorganic fertilizer and periodic liming. The regulated water exchange in T3, showed improved water quality and crop performance (P<0.05) over the zero water exchange, T1. Evaporation loss contributed significantly to CWU (2.9-3.1 m3 water kg-1 production) followed by seepage losses. Regulated water exchange and low apparent feed conversion ratio, helped in lowering the sedimentation rate (54.6-62.8 m3 t-1 biomass). Higher net total water productivity (Rs. 4.4 m-3), net consumptive water productivity (Rs. 8.5 m-3) and ratio of the output value to the cost of cultivation (OV: CC, 2.15) also inferred that T3 had a distinct edge over T1 and T2. In general, total water use varied greatly in aquaculture depending mainly upon the culture method used.